Polemik Penamaan Restoran â€œBabiamboâ€ dan Hubungannya dengan Filosofi Minangkabau â€œAdaik Basandi Syarak, Syarak Basandi Kitabullahâ€: Sebuah Studi Linguistik Forensik: Sebuah Studi Linguistik Forensik - Intan Kusuma Wulandari (Balai Bahasa Provinsi Riau, 2024)
Urang Awak 'Orang Minang' is an ethnicity in West Sumatra Province, Indonesia, and is also widely known for its traditional food in Padang Restaurant. The naming of the Babiambo restaurant in Jakarta which is identified as a typical Minang Babiambo restaurant, babi 'babi' and ambo 'saya' (my pig) is allegedly considered an insult to the identity of the Minang people. This study discusses the naming of the restaurant